How Do Schools and Community Influence Indigenous Youth's Perceptions of English? - Tacio, Liaa Eve Dalilis; Pelila, John Rey Osben (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The increasing dominance of English in academic and social settings has significant implications for Indigenous youth, where language use in both community and school environments influences their opportunities for success and their cultural identity. This study aims to examine the impact of English proficiency on the cultural identity and language use of Indigenous youth in La Trinidad, a town in the Benguet province, Philippines, focusing on how English affects their academic achievement, social interactions, and relationships with their community. Through qualitative interviews with nine Indigenous youth, the study explores their experiences with English and Indigenous languages in daily life, school, and extracurricular activities. The findings show that while English is valued for academic success and social mobility, its dominance leads to the marginalization of Indigenous languages, causing cultural disconnection and generational divides. It is concluded that the promotion of English proficiency, though beneficial in many ways, threatens the survival of Indigenous languages and cultural heritage. To address these challenges, it is recommended that bilingual or multilingual educational programs be introduced in schools and communities to support both English language development and the preservation of Indigenous languages, ensuring that cultural identity is maintained alongside academic and professional advancement.